The effect of a robotics program on primary school students’ attitude towards science and problem solving - Thiwagar A/L Muniandy (2022)
This study was conducted to see the effect of robotics program on primary school students’ attitude towards science and problem solving. Students interest towards science and mathematics already lacking as early of primary school because of less engagement in teaching and learning. There are less hands on teaching in primary school compare to secondary and tertiary education. This has lead to primary school students’ attitude towards science and problem solving lacking. Besides that, studies related to Integrated STEM Approach with students attitude at primary school level are still lacking and it is largely focused on higher institutions. Hence, this study has been carried out to see the effect of robotics program on primary school students’ attitude towards science and problem solving. This study uses a quantitative approach method with a quasi-experimental design involving treatment group (Malacca schools students) and control group (Selangor schools students). A total of 374 primary school students from year six under Ministry of Education Malaysia from Malacca and Selangor were involved in this study. Two questionnaires were used, namely the Test of Science Related Attitudes (TOSRA) was used to measure the attitude towards science of students as well as the Solving Problem Survey questionnaire on attitude towards problem solving. The statistical tests performed were the Repeated Analysis of variance (ANOVA), and One-way Analysis of Covariance (ANCOVA) at a significant level of p <0.05. Researcher looked at the Mauchly’s test for Sphericity as well as subject effect size because the measurements were performed at three different time periods (pre-test, post-test 1 and post-test 2). The results of the analysis showed that the treatment group (Malacca schools students) and control group showed significant changes in the three time periods. Yet the researcher looked at the subject effect size value, which showed the treatment group was higher than the control group. For attitude towards science and problem solving experiment group showed significant changes when compared with the control group.It is suggested that the robotics program can be applied to see improvement in primary school students attitude towards science and problem solving. However, this method needs to be tested using other attitudes so that the effect of robotics program can be seen more holistically.